2013
DOI: 10.3141/2360-02
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Thermographic Inspection of Concrete Bridge Components in Shaded Conditions

Abstract: Infrared thermography has the potential to detect subsurface delaminations before spalling develops and could be used to improve the visual inspection of concrete bridges. The technology has traditionally been applied to bridge decks, which are exposed to radiant heating from the sun that helps develop the necessary thermal gradients in the concrete. Thermal gradients can also be developed from normal diurnal temperature variations. Convective heat transfer develops the thermal gradients, although these therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 6 publications
1
45
0
Order By: Relevance
“…The reason for this is that, during the day, a warming trend existed such that the targets had positive thermal contrasts, which meant that the delaminated regions were at a temperature higher than that of the sound concrete. This is the anticipated behavior based on the fundamental heat transfer theories and complies with previous results reported by Washer et al (2013) and Chase et al (2015).…”
Section: Irt Results and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The reason for this is that, during the day, a warming trend existed such that the targets had positive thermal contrasts, which meant that the delaminated regions were at a temperature higher than that of the sound concrete. This is the anticipated behavior based on the fundamental heat transfer theories and complies with previous results reported by Washer et al (2013) and Chase et al (2015).…”
Section: Irt Results and Discussionsupporting
confidence: 92%
“…For instance, Maser et al (2009) reported that in most bridge structures, areas of severe corrosion are associated with delamination even if cracks are not detected directly. Washer et al (2013) reported that not all delamination can be observed in GPR images and both GPR and IRT can be used together for accurate identification of anomalies in highway bridges. The hammer sounding results showed 40% total delaminated areas on the bridge deck (40% of the total delaminations is common between these two surveys).…”
Section: Validation With Other Techniquesmentioning
confidence: 99%
“…Since concrete structures do not always have homogeneous temperatures due to differences of locations and orientations with respect to the sun as discussed by Washer et al [4], sometimes IRT makes it difficult to interpret the data from raw IR images due to a lot of noise depending on the time of photography as reported in [5]. As Washer et al [19] argued, if the temperature span for IR images is setup around 2°C, while some defects can be detected clearly, some anomalies generate higher/lower temperature than the temperature span and IRT cannot detect them at the temperature span. Therefore, they recommended adjusting the temperature span of IRT continuously throughout inspections.…”
Section: Literature Reviewmentioning
confidence: 90%
“…Furthermore, delaminated areas are enclosed by dotted line. The temperature range of the IR images was set up to 3.0 K for all images as Washer et al suggested in [19], and the level setting was adjusted manually for each IR image to figure out the color contrast between the middle and surrounding areas.…”
Section: Comparison Of Ir Imagesmentioning
confidence: 99%
“…Thermography is often used to search for voids or delamination in concrete because the thermal properties of air are quite disparate from those of concrete. This type of NDE testing will be discussed in section 4.3.3 below in regards to potential delamination of the FRP shell (Washer, Fenwick & Nelson, 2013).…”
Section: Active Thermographymentioning
confidence: 99%